COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN WISATA BERKELANJUTAN DI KABUPATEN KULON PROGO (STUDI KASUS: WISATA KEBUN TEH NGLINGGO) - Iman Surya; Sanny Nofrima; Herdin Arie Saputra; Niken Nurmiyati (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2021)
Abstract: The concept of Collaborative Government as an alternative base is considered capable of realizing the acceleration and implementation of Tourism Areas. Collaborative Governance as a new paradigm used to face diverse issues in a complex society, a paradigm in which the principle of prnsip basically the existence of equality of relationships among stakeholders in the public, private and public sectors. It is also a process that involves various stakeholders who are related for the benefit or achieving a goal. This study analyzed Collaborative Governance in Sustainable Tourism Management, especially in Nglinggo Tea Plantation Tourism Kulon Progo Regency. Then, this research uses qualitative research method. The research results of Nglinggo Tea Plantation Tourism Kulon Progo Regency is one of the sources of income for local communities with the level of tourists visiting tourism to also increase people's income.Keywords: Collaborative government, Sustainable; Tourism